Enhancing the Capacity of Sidomulyo Tourism Village Managers Through Technical Training on Developing Tourism Packages Based on Village Tourism Potential - Bagus Indra Tjayadhi; Kukuh Pribadi (Journal Of Humanities Community Empowerment, 2025)
Tourism villages have become an appealing option for travelers seeking outdoor experiences while engaging with the daily life of rural communities. Sidomulyo Village, located in Silo District, Jember Regency, is one of the tourism villages that offers diverse natural and cultural attractions. Despite its rich potential, the village managers particularly the Tourism Awareness Group (Pokdarwis) still face challenges in packaging these attractions into structured and marketable tour packages. Developing tour packages requires technical skills, including mapping tourism attractions, designing route sequences, estimating travel time, and calculating realistic costs. This community service program was carried out to enhance the capacity of Pokdarwis members in understanding tour package concepts, creating itinerary plans, and practicing basic guiding techniques. The program began with an introductory session on identifying village tourism potential, followed by technical training and hands-on assistance. Through this series of activities, participants not only gained theoretical insights but were also able to create one-day tour packages and overnight tour programs. The results indicate an improvement in participants’ knowledge and skills in transforming local tourism potential into more structured tourism products. This program is expected to strengthen the readiness of Sidomulyo Tourism Village to promote its attractions more effectively and contribute to the development of community-based tourism in the region